Posterior Reversible Encephalopathy Syndrome in Guillain-Barré Syndrome: A Case Report - Jankauskaitė, Gabrielė; Žemgulyė, Gintarė; Balnytė, Renata (Neurologijos seminarai, 2024)
Guillain-Barré Syndrome (GBS) is an acute, immune-mediated neuropathy of the peripheral nervous system, characterized by rapidly progressive, symmetrical weakness of the limbs and the reduction or absence of tendon reflexes. GBS is a rare neurological disorder diagnosed based on the clinical history, neurological examination, cerebrospinal fluid analysis and electroneuromyography (ENMG). In rare cases, GBS can occur together with other syndromes. Posterior Reversible Encephalopathy Syndrome (PRES) is a clinical-radiological condition defined by acute neurological symptoms and characteristic imaging findings. The manifestation of these syndromes may be influenced by congenital Klippel-Feil Syndrome (KFS), which is diagnosed by imaging studies observing fusion of at least two vertebrae of the cervical spine. This syndrome can lead to spinal canal stenosis, reduced neck mobility, and a lower hairline. In this article, we present a 72-year-old female patient who presented to the Emergency Department due to impaired speech and disorientation. Neurological examination revealed findings consistent with encephalopathy. Detailed diagnostic evaluation confirmed a diagnosis of GBS presenting with PRES, accompanied by KFS. This case illustrates the diversity of clinical symptoms in GBS and highlights the importance of a comprehensive differential diagnosis when evaluating patients with suspected demyelinating polyneuropathy.